Transition time threshold for Double Cantilever Beam specimens under high loading rates. (15th May 2021) - Medina, S.A.; González, E.V.; Blanco, N.
Abstract: Inertial force effects complicate the determination of the mode I interlaminar fracture toughness under high loading rates in composites. Although using a quasi-static analysis is a common approach, it is not always valid. A time-based threshold criterion is proposed to determine when dynamic effects might be neglected during the analysis of a high loading rate Double Cantilever Beam test. The criterion compares a transition time, time after which inertia effects can be neglected, versus the time for the initiation of fracture propagation. Three different methods are considered for the transition time. Good agreement is found when comparing the expressions with numerical simulations. It is also demonstrated that the transition time is affected by the velocity profile. The proposed criterion and approach to determine the transition time are useful tools to define when a quasi-static data-reduction scheme can be used. Highlights: A threshold criterion is proposed to use a QS analysis in a high loading rate DCB test. Three different methods to obtain the transition time for a DCB test are presented. Dimensional study to develop a numerically-based expression for the transition time. Assessment of the loading velocity effects over the transition time.